Effect of the eQuality Health Bwindi Scheme on Utilization of Health Services at Bwindi Community Hospital in Uganda - Agasha, Doreen Birungi; Edwin, Birungi Mutahunga R.; Baine, Sebastian Olikira (Frontiers in Public Health, 2019)
Introduction eQuality Health Bwindi (eQHB), a Community Based Health Insurance (CBHI) scheme was launched in March 2010 with the aim of generating income to maintain high quality care as well as increasing access to and utilization of health services at Bwindi Community Hospital (BCH). The objective of this study was to document evidence of the effect of eQuality Health Bwindi Scheme on access and utilization of health services to inform decision making, policy and scale up of the scheme. Methods and Materials This study applied qualitative and quantitative research methods. It involved a review of hospital records for the period July 2009 – June 2014, a survey of 272 households, four focus group discussions, and six key informant interviews. Both quantitative and qualitative analysis techniques were applied. Results Outpatient attendance, inpatient admissions, and deliveries at the hospital increased by 65%, 73% and 27% respectively between FY 2009/10 and FY 2012/13. Utilization of health services by sick children from insured participants was greater than that of the uninsured members of the community (p-value = 0.0038). BCH services became more affordable. However, opting out of the scheme at a later stage in the review period was attributed to rising unaffordable premiums and co-payments. Failure to afford scheme membership, residing far from BCH and limited understanding of health insurance led to reduced BCH service utilisation. Conclusions eQuality Health Bwindi has potential to increase access and utilization of health services at BCH. The challenges are; limited understanding of the concept of health insurance and unaffordable premiums and co-payments set to enable provision of high quality services. Recommendations In order to increase eQHB coverage and utilization of BCH, we recommend; continuous community sensitization on the health insurance concept, establishment of satellite health facilities closer to members, transformation of eQHB to a savings and credit society with potential to grow savings and in the long run reduce premiums, enlargement of partnerships for funding and a further study to establish ways in which premiums and copayments in a CBHI scheme can be increased without negatively affecting membership, quality and utilization of health services at BCH.